O peso da vergonha e o corpo gordo dos homens - Santana, João Paulo Corumba de (2021)
The body has been, in contemporary times, the target of increasingly abusive social demands, concerning its “aesthetic” existence. This work is about the shame some men feel about their fat bodies. Our research subject, therefore, is men who feel ashamed of their fat bodies, increasingly stigmatized by a standardized imposition of beauty marked by a muscular appearance, driven by market niches. In the face of such a state of affairs, it is worth asking: What are the implications of the shame of the fat body in the affective life of men? The applied methodology is supported by documental analysis of clinical fragments, from mnemic records produced by the analyst himself, postsessions.he affective life of men? We carried out a bibliographical analysis of important theorists of psychology, psychoanalysis, sociology and history such as Sigmund Freud, Georges Vigarello, Yves de La Taille, Julio Vertzman, Vincent de Gaulejac, David Le Breton, among others. The objective of this work is to contribute to the study about the shame of the fat body, starting from the narratives collected in the psychoanalysis sessions, focusing on the developments of this issue, in the psychological, psychoanalytic, sociological and historical perspectives, in order to bring to the public the debate about the implications of fat body shame in men's affective lives. Thus, taking into account the records used, we postulate three categories of analysis to better elucidate the sufferings that come from the shame of the fat body, such as: “shame and embarrassment: the fat body between inhibitions and ideals”; “corpolatry: from muscular appearance to self-loathing”; “fat body and debility: shame and its fate”.